The Development of the Logistics Transportation Management Prototype System: A Case Study of the Economic Development along the East-West Economic Corridorin Thailand - Pattama Charoenporn (My University, 2022)
The objective of this research is to design a logistic transportation management system prototype that can manage operations through a one-stop service. The development of the prototype will be utilizing a Saving Algorithm and Google Map to help analyze routes and determine the lowest cost. The design of the various functions will be based on samples of the transportation data of the East-West Economic Corridor. The research’s data collection will be based on data obtained from 400 transport and logistical operator samples, professionals who possess knowledge related to logistic transportation management, or academics who are well- versed in logistic operations. The collection of data was conducted using questionnaires, which were used to conduct interviews before the design of the prototype, and thereafter, to evaluate the completed logistic system design. As a result of the data collection, the researcher was then able to use the information obtained to design the interface of the logistic transportation management prototype system, which was able to comprehensively define the various functions of the prototype system. The results from testing the system based on the ISO 9241-151 principles showed that the detailed layout of the screens was rated to be Very Good by 4 persons, while 2 persons rated it as Fair. The reason that it was rated as Fair was due to the details of the proposed content was not very comprehensive as expected. As for the aspect of searching for information, it was rated as Very Good by 2 points, The display of the contents and details of the system function, such as fonts or colors, were rated to be Very Good by 3 points, and Good by 2 points. Experts commented that the system should be able to provide more details in explaining the functions of the different menus on each page or adding a navigator for other topics, such as the system processing speed. The system’s processing function was rated as Good by 3 points and Fair by 2 points.Finally, the results show that, the prototype has presented guidelines for applying the concepts of both algorithms to work collaboratively with the logistics system.It canhelp transporter to find the route of travel as well. Keywords— Smart and intelligent computing, logistic system, Economic Development, East-West Economic Corridor
Keywords: Urban Transport Systems Analysis